Study on the effect of space tightness on the inerting effect of liquid CO2 in pottery jar liquor warehouses - Xueming Li; Wei Wan; Gang Bai; Youkai Zhao; Xunxian Shi; Jinsong Zhu (Scientific Reports)
Abstract To investigate the effect of space tightness on inerting of liquid CO2. Pottery jar liquor warehouse was selected as the research subject, numerical simulation was utilized to study the spatial inerting and CO2 migration and distribution under different space tightness degrees and injection flow rates. The results revealed that after injection into the space, CO2 distributed like an “umbrella”, the CO2 protective layer undergoes a dynamic process of concentration increase and thickness enhancement, achieving upward accumulation and migration of the inert medium protective layer. The space was divided into direct inerting zone, CO2 accumulation zone and accumulation zone, with an effective inerting diameter of approximately 2 m for the direct inerting zone. When the fire extinguishing system is activated in the fire source space for 60 s, the O2 concentration at Z = 0.3 m decreases to less than 10%, and the CO2 inerting rate exceeds 98%. The space inerting effect increased with the injection flow and space tightness, whereas the effective inerting rate decreased with the space height and injection time. After 60 s of injection, the leakage reached the maximum, about 1.0 ~ 1.2 kg/s. It could improve liquid CO2 utilization by reducing the injection flow rate or enhancing space tightness. Based on this, a design concept of liquid CO2 intelligent control fire extinguishing system is proposed.